Capillary zone electrophoresis in phosphate buffer--known or unknown? - Gebauer, P; Pantůiková, P; Bocek, P (Journal of chromatography. A, 2000)
It has been shown recently that the analysis records in capillary electrophoresis may involve regions with extremely strong electromigration dispersion of peaks. Such a fundamental effect is due to the existence of more centers of symmetry in a given electrolyte system. This paper shows that even such a simple and frequently used electrolyte system as phosphate buffer may exhibit more than one center of symmetry. By using the peak shape diagram approach we have revealed that neutral and alkaline phosphate buffers have two centers of symmetry and one center of extreme dispersion. Model experiments confirmed this new important discovery.
Keywords: Phosphates; Buffers; pufry; fosfáty; Electrophoresis, Capillary; elektroforéza kapilární